The impact of excess body fat on bone remodeling in adolescents. Issue 3 (March 2017) - Mosca, L.; Goldberg, T.; Silva, V.; Kurokawa, C.; Rizzo, A.; Silva, C.; Santos Teixeira, A.; Corrente, J.
Abstract Summary The impact of excess body fat on bone remodeling was evaluated in overweight, obese, and extremely obese adolescents. In adolescents with excess weight, it was observed that the higher the bone mineral content and bone mineral density values, the lower the levels of the biomarkers. Nutritional imbalances by excess had a negative effect on bone formation in this stage of life. Introduction The aim of this study was to investigate the impact of excess body fat on bone remodeling in adolescents. Methods Body weight, height, and body mass index were determined in 391 adolescents classified as normal weight, overweight, obese, and extremely obese. Bone age was obtained and bone mineral content and bone mineral density were evaluated in the lumbar spine, proximal femur, and total and subtotal body. Blood samples were collected for evaluation of the following bone biomarkers: osteocalcin, bone alkaline phosphatase (BAP), and serum carboxy-terminal telopeptide (S-CTx). The data were analyzed according to nutritional status and age. Results In girls with excess weight, the biomarkers were higher in the 10 to 13-year age group and no significant differences were observed between groups according to nutritional status. In boys, the levels were higher in those aged 13 to 15 years. According to nutritional status, significant differences were only observed in mean S-CTx for the age groups of 10–15 years, with higher levels between overweight and obese adolescents aged 10–12 years and between obese and extremely obese adolescents aged 13–15 years. In girls, significant negative correlations were observed between lean mass, fat mass, and fat percentage and each of the three bone markers studied. There was no correlation between lean mass or fat mass and the three biomarkers in boys. The biomarker trends demonstrated across the age groups follow the age trends for growth velocity. Conclusions The higher the fat percentage and fat mass in girls, the lower the levels of the biomarkers, indicating that excess body fat has a negative effect on the evolution of these markers during adolescence.